Green development level assessment and obstacle analysis of China's coal-resource-based regions - Chun, Yutong; Zhang, Jun; Han, Yijie (Heliyon, 2023)
Coal is the main source of energy in China, however, in the context of carbon neutrality, how coal-resource-based regions can not only undertake the national supply of terminal energy and industrial raw materials, but also achieve regional green development is an important issue. In this paper, first, we constructed a green development indicator system for coal-resource-based regions named the green development indicator system of coal-resource-based regions (GDISCR), which could coordinate the relationship among the economy, energy, and environment when evaluating the green development level. Second, we proposed a new evaluation model named dynamic spatial TOPSIS, which comprehensively considered the spatial differences of research subjects and the differences over time in the evaluation process. Third, we introduced the obstacle analysis model to find the obstacle factors preventing green development of coal-resource-based regions. Finally, we evaluated ten coal-resource-based provinces to evaluate their green growth levels and demonstrate the effectiveness of our methodology. The following were the major conclusions: (1) The average comprehensive evaluation value of the 10 coal-resource-based provinces was 0.3956, based on which the coal-resource-based provinces could be divided into two types, namely, provinces with better or worse green development levels. (2) The obstacles restricting the green development of provinces with coal resources were dynamic, but the importance of an obstacle factor for provinces was relatively fixed. (3) The greatest obstacle to the green development of provinces with coal resources was technological capacity in the economy, with an average obstacle degree of 27.48% in 2022, and they had similar difficulties in energy transition but different difficulties in environmental protection. On the basis of these findings, some feasible recommendations for the environmentally friendly growth of coal-resource-based provinces are discussed.